Integration of Hybrid Musical Instruments into Russian Piano School - Irina V. Malykhina (National Research Mordova State University, 2019)
Introduction. The article presents the introduction of the hybrid musical instrument (disklavier) into the system of Russian music education. This new instrument has appeared relatively recently. It is relevant to study the world experience of using the hybrid piano and to analyze the prospects for applying it in the field of Russian piano performance. The purpose of the article is to analyze the specifics of using the hybrid musical instrument with additional equipment among students of higher educational institutions of Moscow. Materials and Methods. In the experimental part of the study, the American method of K. Riley was used. The additional techniques of working with disklavier and additional equipment based on Riley's method were developed and applied. An activity criterion was chosen to assess the professional ski lls of students. Results. Based on pedagogical observation and interviewing, it was established that the use of a hybrid musical instrument and additional equipment improves the intellectual, research and creative abilities of students. The disklavier allows students to hear themselves in acoustic format from the position of a teacher. The instrument provides auditory and visual analysis of performance. The students can compare their feelings from the game with the exact data recorded by the disklavier and make changes to the record without losing its quality. Discussion and Conclusion. The study demonstrates the effectiveness of the use of specially developed methods of working with the disklavier and additional equipment. More work will need to be done to determine the influence of new technologies in the class of a special piano and chamber ensemble at various levels of education. This study may be of interest both for students and teachers of the piano department at secondary special and higher educational institutions.